2018
DOI: 10.3892/mmr.2018.8649
|View full text |Cite
|
Sign up to set email alerts
|

Association of the PPARγ/PI3K/Akt pathway with the cardioprotective effects of tacrolimus in myocardial ischemic/reperfusion injury

Abstract: Myocardial ischemia/reperfusion injury (MIRI) induces severe arrhythmias and has a high risk of mortality. The aim of the present study was to investigate the effect of tacrolimus on arrhythmias, cardiac function, oxidative stress and myocardium apoptosis induced by MIRI, and to elucidate the underlying mechanism. The effects of MIRI and tacrolimus on arrhythmias, cardiac function parameters, myocardial oxidative stress and apoptosis were investigated in a rat model of MIRI. The phosphorylation of peroxisome p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Nrf2 and eNOS are both modulated by the PI3K/Akt signalling pathway, the activation of which plays a pivotal role in cellular homeostasis under oxidative stress 27 . We have been suggested that Gas exerted its protective effects through a mechanism dependent on PI3K/Akt, which, based on our results above, indicated that Gas exerted its effect through the Cav‐1/eNOS and Nrf2/ARE pathways.…”
Section: Resultssupporting
confidence: 56%
“…Nrf2 and eNOS are both modulated by the PI3K/Akt signalling pathway, the activation of which plays a pivotal role in cellular homeostasis under oxidative stress 27 . We have been suggested that Gas exerted its protective effects through a mechanism dependent on PI3K/Akt, which, based on our results above, indicated that Gas exerted its effect through the Cav‐1/eNOS and Nrf2/ARE pathways.…”
Section: Resultssupporting
confidence: 56%
“…For example, phosphatase PTEN that negatively regulates the PI3K/Akt pathway can be inhibited by ROS [234,235], exosomes derived from bone marrow stromal cells [236], or Achyranthes bidentata polypeptides [237], then enhancing Akt phosphorylation and promoting myocardial protection. Treatments targeting PI3K/Akt or related signaling pathways reduce reperfusion complications such as arrhythmias [238,239], myocardial stunning [239], myocardial no-reflow [240], and adverse remodeling [241]. [19,[91][92][93][94].…”
Section: Regulation Of the Oxidation Defense Systemmentioning
confidence: 99%
“…Experimental studies have indicated that intervention and ischemia preconditioning using some pharmacological agents can recruit the PI3K/Akt pathway and confer powerful cardioprotection [13]. It has been proposed that pharmacological targeting of the Akt pathway may potentially diminish ischemia reperfusion (IR) injury [14].…”
Section: Introductionmentioning
confidence: 99%